Features of the Centers of Academic Success in US Universities - Tsymbaliuk, Svitlana (Educological discourse, 2023)
The article reviews the peculiarities of Academic Success Centers (ASC) in US universities. In this regard, the concept of "student success" was analyzed, it was found that this concept is directly related to academic achievements, in particular, academic success. There is no single definition of the term "academic success center" in scientific discourse today. This is related to the academic autonomy of higher education institutions, which independently determine the range of services and support programs for students in such centers. A study of the practices of the best private and public universities in the United States showed that most of these institutions of higher education have centers of academic success in their structure. These structural subdivisions direct their activities, first of all, to ensure academic support and retention of the student contingent of the educational institution. It was found that the main technologies for supporting the academic success of students are tutoring, academic coaching and mentoring. Special attention is payed on interaction with students of the first year of study (freshmen), who most often face a number of problems in a new academic environment for them (adaptation to new conditions, change of lifestyle, choice of profession, new acquaintances). Centers for academic success provide an opportunity not only to learn, but also to teach. Senior students have the opportunity to become tutors, mentors and academic coaches. Such practice allows them to strengthen their own knowledge base, acquire new skills and take the first step in your career. Another feature of academic success centers is conducting career guidance work with applicants. Universities specially organize meetings of future freshmen with students, graduates, teachers and administration of the institution to provide complete information about admission, studies and further employment prospects. Attention is paid to the development of university campus culture and the involvement of education seekers in student communities. Providing socio-psychological support is one of the important areas of activity of centers of academic success, because it is important for students to develop self-awareness, self-confidence in order to become independent and fully reveal their academic, professional and personal potential. The conducted study actualized the need for a thorough research of the basic principles of the areas of activity of centers of academic success in US universities in order to introduce better experience into the educational practice of domestic universities.